PENGARUH LITERASI KEUANGAN TERHADAP INKLUSI KEUANGAN DENGAN FINANCIAL TECHNOLOGY SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Budi Luhur) - Alvina Marcellina; Sugeng Priyanto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study ains to determine the effect of financial literacy on financial inclusion with financial technology as a mediating variable among students of the Faculty of Economics and Business, Budi Luhur University. The research method used is explanatory research with a quantitative approach. The data analysis technique used in this study is Structural Equation Modeling–Partial Least Square (SEM-PLS). Sampling in this study used purposive sampling with a sample size of 96 students. Data were collected through questionnaires and processed using SmartPLS v.4.1.1.6 software. The results showed that financial literacy and financial technology had a positive and significant effect on financial incluasion. Financial literacy had a positive and significant effect on financial technology. Financial technology is able to mediate the effect of financial literacy on financial inclusion among students of the Faculty of Economics and Business, Budi Luhur University. Increasing financial inclusion among students does not only depend on financial literacy, but also on the ability to utilize financial technology appropriately. Therefore, the integration of financial literacy and the use of financial technology is necessary so that students can access formal financial services more effectively.